Alcohol Use during the COVID-19 Pandemic: Self-Reported Changes and Motives for Change - Bramness, Jørgen G. (Eur Addict Res, 2021)
BACKGROUND: In Europe, the COVID-19 pandemic triggered a range of restrictive measures, which may have impacted alcohol consumption. OBJECTIVES: We explored perceived changes in alcohol consumption, their association with sociodemographic characteristics and past year alcohol consumption, and self-reported reasons for change after COVID-19 restrictions in Norway. METHOD: A web-based survey was sent to Norwegians aged 18 years and older in June–July 2020. Respondents reporting any past year alcohol use (n = 1,200) were asked whether they drank less, approximately the same, or more after the COVID-19 restrictions compared to before and reasons for drinking less or more. RESULTS: Almost a third (29.9%) reported they drank less, whereas 13.3% reported they drank more. Females, younger respondents, and Oslo residents were more likely to report both less and more drinking (p values between 0.001 and 0.029). Past year alcohol use was associated with less drinking (OR = 0.93; p < 0.001) and more drinking (OR = 1.07; p < 0.001). More drinking was also associated with living with child(ren) (p = 0.023) and high educational level (p = 0.029). The most frequently reported reasons for drinking less pertained to fewer social occasions and less on-premise drinking, whereas reasons for drinking more pertained to treating oneself to something good and fewer consequences of drinking more. CONCLUSIONS: After the COVID-19 restrictions were implemented, a substantial proportion of Norwegians changed their drinking behaviour.